Теоретичні основи застосування стратегій навчання іноземної мови - Сіладі Василь; Siladi Vasyl; Szilágyi László (Bидавництво МДУ, 2019)
Резюме. Мета дослідження полягає в підкресленні важливості стратегій під час вивчення іноземної мови та її викладання. Робота узагальнює наявні відомості із стратегій вивчення мови, дає визначення поняття стратегії вивчення мови й окреслює таксономію стратегій вивчення мови, запропоновану провідними дослідниками у цій галузі. Визначено роль учителя взастосуванні методики стратегій і наведено низку проблем для подальшого вивчення стратегій вивчення мови.

Abstract. The purpose of the study is to emphasize the importance of strategies for learning a foreign language and its teaching, the essence of which is to study the problem as students process new information and strategies of which type are used to interpret, study and memorize new information. The work generalizes available information from the strategies of language learning, defines the concept of a language learning strategy, and outlines the taxonomy of language learning strategies proposed by leading researchers in this field. The classification of strategies for learning a foreign language is substantiated: J. Rubin (learning strategies, communicative strategies, social strategies), R. Oxford (metacognitive strategies help students regulate their own learning process, affective strategies are related to the student's emotional requirements, and social strategies lead to intense interaction with the target language, cognitive strategies - these are the mental strategies that contribute to understanding the learning of learners, strategies for remembering), taxonomy of strategies for learning the language of R. Oxford (direct links strategy, indirect strategy), J. O'Malley: metacognitive strategy; cognitive strategies; socio-affective strategies, H. Stern distinguishes five main strategies for language learning: strategies of management and planning, cognitive strategies, communicative - strategies of experience, interpersonal strategies, affective strategies. The role of the teacher in the application of strategy techniques is determined, in particular, it is necessary to provide a wide range of training strategies in order to match the style of learning, the students' preference for motivation, strategies, analyze the textbook they use in the audience and identify or contain strategies for learning the language and their learning to analyze their own methods teaching and general style of behavior in the audience. To the teacher who wants to familiarize his students with the strategies for learning the language, you must first study the interests, motivation and style of learning the students. It is concluded that language learning strategies that include specific actions, behaviors, tactics or techniques help learners to learn the target language.

Резюме. Цель исследования заключается в подчеркивании важности стратегий при изучении иностранного языка и его преподавания. Работа обобщает имеющиеся сведения из стратегий изучения языка, дает определение понятия стратегии изучения языка и определяет таксономии стратегий изучения языка, предложенную ведущими исследователями в этой области. Определена роль учителя в применении методики стратегий и приводит ряд проблем для дальнейшего изучения стратегий изучения языка.
Theoretical basis of implementation of strategies of foreign language teaching
https://pp-msu.com.ua/uk/article/teoretichni-osnovi-zastosuvannya-strategiy-navchannya-inozemnoyi-movi
Keywords: стратегії навчання іноземної мови; когнітивні стратегії; класифікації стратегій